2018
DOI: 10.2147/ott.s152217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on the risk and survival of nasopharyngeal carcinoma: a meta-analysis

Abstract: BackgroundDiabetes mellitus (DM) has been identified to be both a risk factor and a prognostic factor in a variety of malignancies, but its association with the risk and outcome of nasopharyngeal carcinoma (NPC) is still unclear. To elucidate this issue, we systematically reviewed the evidence concerning the association between DM status and NPC.Materials and methodsWe identified studies by a literature search of PubMed, Embase, and ISI Web of Knowledge through May 31, 2017, and by searching the reference list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“… 23 , 24 A meta-analysis of nine studies showed that diabetes has no impact on NPC prognosis. 25 However, a recent case-control study showed that patients with diabetes have shorter survival than those without diabetes. 26 The prognostic value of different lipoproteins in NPC is different, among which high-density lipoprotein and apolipoprotein A-I are favourable prognosticators, while low-density lipoprotein is an indicator of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 A meta-analysis of nine studies showed that diabetes has no impact on NPC prognosis. 25 However, a recent case-control study showed that patients with diabetes have shorter survival than those without diabetes. 26 The prognostic value of different lipoproteins in NPC is different, among which high-density lipoprotein and apolipoprotein A-I are favourable prognosticators, while low-density lipoprotein is an indicator of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it can achieve targeted control of blood sugar in diabetic patients, prevent the evolution of diabetes, and reduce the risk of complications. Glycosylated hemoglobin is generally not affected by daily fluctuations in disease, life stress and environment, which just shows blood glucose levels (12)(13). For diabetes, there are also recommendations for the use of medicinal herbs (14).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that hypertension is associated with the risk of oral cavity and laryngeal cancer [ 27 ], and metabolic syndromes are significantly associated with the risk of laryngeal cancer [ 28 ]. By contrast, no overall association was identified between metabolic disorders and NPC [ 29 ], except for a previous study that reported an inverse association between diabetes and NPC [ 30 ]. Our report demonstrated a positive association between the glycated hemoglobin level and the risk of significant CAS development in Cox regression model.…”
Section: Discussionmentioning
confidence: 99%